Factor Influencing Intention Repeat Tourism to Visit Singapore in New Normal based on Indonesia Traveler’s - Chun Wang; Yang Zhu; Grida Saktian Laksito (Research Collaboration Community (RCC), 2022)
The Covid-19 pandemic which has spread in various countries has a severe impact on all sectors in every country, especially the economic and tourism sectors. One of which is Singapore, which has closed access to foreign tourism with a lockdown policy and has progressively implemented a series of steps to reduce the risk of a wider spread of the COVID-19 pandemic in the community. Singapore has managed to maintain sustainable tourism over the years. Several tourist attractions in Singapore have resumed operations after being closed for several months. Indonesia was the market for the first largest source of income from tourism for Singapore for five consecutive years in 2016. This study aims to determine the perception of Indonesian travelers to return to tourism after the Singapore government reopened tourism to foreign countries. The research method used is quantitative, the sampling technique uses non-probability sampling and a sample of 285 respondents is obtained. The analytical tool used Path analysis and the hypothesis uses a significance test using the Partial Least Square Structural Equation Model (PLS SEM). The results of this study indicate that destination attractiveness, tourist motivation, accessibility, and risk perception can directly revisit the intention of Indonesian tourists to travel in Singapore. Then, destination attractiveness and tourist motivation can affect the revisit intention of Indonesian tourists to travel back to Singapore after the Covid-19 outbreak.